GPCRs that Rh oar the Guanine nucleotide exchange factors - Omble, Aishwarya; Kulkarni, Kiran (Small GTPases, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Cell migration, a crucial step in numerous biological processes, is tightly regulated in space and time. Cells employ Rho GTPases, primarily Rho, Rac, and Cdc42, to regulate their motility. Like other small G proteins, Rho GTPases function as biomolecular switches in regulating cell migration by operating between GDP bound 'OFF' and GTP bound 'ON' states. Guanine nucleotide exchange factors (GEFs) catalyse the shuttling of GTPases from OFF to ON state. G protein-coupled receptors (GPCRs) are the largest family of cell surface receptors that are involved in many signalling phenomena including cell survival and cell migration events. In this review, we summarize signalling mechanisms, involving GPCRs, leading to the activation of RhoGEFs. GPCRs exhibit diverse GEF activation modes that include the interaction of heterotrimeric G protein subunits with different domains of GEFs, phosphorylation, protein-protein interaction, protein-lipid interaction, and/or a combination of these processes.